Targeted and cytotoxic therapies as maintenance treatment for non-transplant eligible patients with acute myeloid leukemia. (November 2021) - Patel, Shyam A.; Litzow, Mark R.; Cerny, Jan
Abstract: In the recent years, there have been multiple approvals by the Food and Drug Administration (FDA) for therapeutics for acute myeloid leukemia (AML). The role of maintenance therapy in AML has been rather unrealized mostly due to lack of efficacy and increased toxicity of classical chemotherapy agents. Many clinical trials have demonstrated a disease-free survival benefit for various therapeutics in the maintenance setting for patients with AML who are ineligible for stem cell transplant. Notably, oral hypomethylating agent therapy has recently shown an overall survival and disease-free survival benefit in the maintenance setting for AML. In this review, we summarize the relevant data on maintenance therapy with a specific focus on cytotoxic antimetabolite chemotherapeutics, hypomethylating agents, targeted agents, and immunotherapeutics. We discuss our approach to maintenance therapy in AML in 2021 and propose a measurable residual disease (MRD)-adapted, personalized approach based on the best available evidence.